THE RELATIONSHIP BETWEEN PHYSICS AND BIOLOGY IN THE STUDY OF THERMODYNAMIC SYSTEMS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The didactic possibilities of teaching physics in connection with biology by high school students of secondary schools on the elementary fundamentals of biophysical science are considered.